Personalized Learning through Differentiation strategy : A Solution in Teaching Arabic Speaking Skills - Ida Miftakhul Jannah; Mohamad Thohir (ALSINATUNA, 2026)
Students of Arabic Language Departement study program have diverse characteristics, including Arabic speaking ability, learning styles, speed of comprehension, and linguistic background. This diversity of student characteristics gives rise to different learning needs, which must be accommodated well. This study aims to describe personalized learning through differentiation strategies in Arabic speaking skills which is still rarely studied and is expected to provide theoretical and practical contributions. This research is a qualitative descriptive. The subjects were 21 students of class A of the kalam lil mubtadiin class first-semester 2025/2026. Data were collected through observation, speaking ability tests, in-depth interviews with students and lecturers, and documentation. Data analysis were processed and analyzed using data reduction, data presentation, and conclusion drawing. The results showed that personalization through this differentiation strategy was carried out with three differentiations: content, process, and product differentiation. This can accommodate all differences in students, both differences in language competency and learning styles. These findings indicate that personalized learning with differentiation strategies not only accommodates individual differences but also creates an inclusive learning environment that supports each student to achieve their maximum potential in Arabic speaking skills.